The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.11648/j.ajac.20180605.12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Activated Carbon from Cow, Donkey, Chicken and Horse Bones from Ezzangbo in Ebonyi State, Nigeria

Abstract: Animal bones have been used to produce carbon char for quality assessment of activated carbon over non activated carbon (used as sample control) as influenced by method of activations (acid and heat). In this study samples analyzed were carbonized in a closed crucible at 400°C and ground into powder after cooling. 200g of each of the crushed samples was activated using 250ml of 2 M Hydrochloric acid for one hour at 80°C and another 200g was activated by thermal method at 120°C for 3 hours. To obtain the optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…On average, a bulk density of 0.46 g/cm 3 was obtained. This value was found in the acceptable range of the carbonaceous materials of 0.35 to 1.2 g/m 3 as reported by many studies (Sunday et al 2018). Normally, high bulk density is considered to be a good quality of the adsorbent materials.…”
Section: Characterization Of Activated Carbonsupporting
confidence: 71%
“…On average, a bulk density of 0.46 g/cm 3 was obtained. This value was found in the acceptable range of the carbonaceous materials of 0.35 to 1.2 g/m 3 as reported by many studies (Sunday et al 2018). Normally, high bulk density is considered to be a good quality of the adsorbent materials.…”
Section: Characterization Of Activated Carbonsupporting
confidence: 71%
“…Adsorbent removal efficiency increases with increased in adsorbent dosage. This is as a result of increased availability of exchangeable sites for the adsorbate [39]. percentage adsorption occurred linearly with increasing temperature.…”
Section: Figure 5 Effect Of Biosorbent Dosage On % Biosorption Of Chmentioning
confidence: 91%
“…The variation of the dosage of the adsorbent mixture as represented in figure 5, showed that, mass increase of the adsorbent dosage causes linear increase of the percentage Biosorption. High mass of the adsorbents would adsorbent higher adsorbate on to their active pore surfaces because of their increased surface area [39]. Maximum adsorption was observed to be 90.30% at 3.00g mass of the adsorbent.…”
Section: Figure 5 Effect Of Biosorbent Dosage On % Biosorption Of Chmentioning
confidence: 98%
“…In conjunction with SEM, the energy dispersive X-ray (EDX) analysis technique was used to perform the elemental analysis and chemical characterization of the material. EDX utilizes an electron beam that strikes the surface of a conducting sample (placed under SEM) to determine its elemental content [28].…”
Section: Methodsmentioning
confidence: 99%